Type I Interferons as Ambiguous Modulators of Chronic Inflammation in the Central Nervous System - Prinz, Marco; Knobeloch, Klaus-Peter (Frontiers in Immunology, 2012)
Type I interferons (IFNs) were originally identified as antiviral effector molecules that exert pleiotropic physiological processes ranging from immune modulation, control of proliferation, apoptosis to antitumor activity. However, type I IFNs were recently also shown to apply both beneficial and detrimental effects to the central nervous system (CNS) and a tightly balanced equilibrium between cellular activation and inhibition seems to be essential to maintain homeostasis within the CNS. In inflammatory pathologies affecting the CNS, type I IFNs are in the centre of attention not only because interferon beta (IFN-b) is used as a standard therapeutic in the treatment of relapsing-remitting multiple sclerosis (MS). Despite the great efficiency of IFN in reducing MS relapses and attenuation of novel inflammatory lesions is well documented, underlying molecular mechanisms and cellular target specificities are just beginning to emerge. In contrast to the curative effects, aberrant activation of the type I IFN response were also recently shown to be associated with detrimental effects exemplified by the Aicardi-Goutières syndrome (AGS), a severe disabling autoimmune inflammatory encephalopathy. This review will highlight the dual role of type I interferons during chronic CNS inflammation. Recently uncovered molecular and cellular mechanisms in the etiology of AGS and experimental autoimmune encephalomyelitis (EAE), the murine model of multiple sclerosis will be highlighted.